Medical Journal of Indonesia Vol.25. Issue 4, Desember 2016, pp 195-266 - Redaksi (FK Universitas Indonesia, 2016)
- Prevalence of Helicobacter pylori among patients with different gastrointestinal disorders in Saudi Arabia - MMP-9, brain edema